Scenario-based Strategic Planning Developing Strategies in an Uncertain World - Schwenker, Burkhard.; Wulf, Torsten. (Roland Berger School of Strategy and Economics,, 2013)
In a world characterized by increasing complexity and volatility, managers must be able to flexibly adapt their strategies to changing environmental conditions. Traditional strategic management frameworks often fail in this context. Therefore, we present "scenario-based strategic planning" as a framework for strategic management in an uncertain world. Previous approaches to scenario planning were complex and focused on the long term, but the approach developed by Roland Berger and the Center for Strategy and Scenario Planning at HHL Leipzig Graduate School of Management is different. By designing appropriate tools and integrating scenario planning into strategic planning, we have made our approach less complex and easier for firms to apply. We illustrate the approach with examples from different industries.   The contents ⬢⬢ We show that traditional strategic planning and forecasting tools are often inadequate when faced with today's fast-changing environments ⬢⬢ We propose scenario-based strategic planning as a powerful strategic planning approach that accounts for uncertainty, volatility and complexity ⬢⬢ We give a detailed description of our new, tool-based approach to scenario-based strategic planning ⬢⬢ We show how our approach works in practice and improves decision quality, fosters flexible strategies and supports good management The target audience Top managers, planning experts, consultants, academics The editors Prof. Dr. Burkhard Schwenker is CEO of Roland Berger Strategy Consultants and Chairman of Roland Berger School of Strategy and Economics. Prof. Dr. Torsten Wulf is Professor of Strategic and International Management at Philipps-University Marburg. Both are Academic Directors of the Center for Strategy and Scenario Planning at HHL Leipzig Graduate School of Management.   About Roland Berger School of Strategy and Economics Roland Berger School of Strategy and Economics (RBSE ) is the corporate university of Roland Berger Strategy Consultants. As a research, knowledge transfer and teaching unit, RBSE's mission is to help business leaders master complexity and set up sustainable strategies. Our book series published by Springer and our other publications present the latest research findings and a unique store of methodological expertise. www.rolandberger.com/rbse.